Validation of the Portuguese Variant of the Munich Chronotype Questionnaire (MCTQPT) - Reis, Cátia (2020)
This work was supported by the Fundação para a Ciência e Tecnologia (FCT) Ph.D. research Grants PDE/BDE/114584/2016 and PDE/BDE/127787/2016 and the Bial Foundation (135/18).